Discord under the influence of a quantum phase transition - 王林成 申健 衣学喜 (Chinese physics B, 2011)
This paper studies the discord of a bipartite two-level system coupling to an XY spin-chain environment in a transverse field and investigates the relationship between the discord property and the environment＇s quantum phase transition. The results Show that the quantum discord is also able to characterize the quantum phase transitions. We also discuss the difference between discord and entanglement, and show that quantum discord may reveal more general information than quantum entanglement for characterizing the environment＇s quantum phase transition.